1990
DOI: 10.1177/0272431690102004
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Relationship between Achievement and Self-Image During Early Adolescence

Abstract: This research tested whether the relationship between school achievement and self-image would show different developmental patterns for girls and boys during early adolescence. The study followed 242 subjects from sixth through eighth grade. Multiple correlations and covariance matrix analyses (LISREL) revealed a stronger positive relationship between school achievement and self-image for boys and girls in sixth grade and especially in seventh grade. Longitudinal analyses of covariance matrices, within gender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 19 publications
4
12
0
Order By: Relevance
“…Although a number of researchers have found that boys perceive themselves as significantly more assertive than girls by early adolescence (Ahlgren & Johnson, 1979;Dusek et al, 1981;Galambos et al, 1990;Leahy & Eiter, 1980;Roberts, Sarigiani, Petersen, & Newman, 1990), others have found no gender differences in adolescent assertiveness, or that adolescent girls report being more assertive or autonomous in their relationships than boys do (Buhrmester et al, 1988;Hibbard, Tao, & White, 1997;Sharabany et al, 1981;Steinberg & Silverberg, 1986). Eccles, Barber, Jozefowicz, Malenchuk, and Vida (1999) found no gender differences in adolescents' self-ratings of leadership or independence while Feldman et al (1981) found that gender differences in assertiveness did not develop until later in life.…”
Section: Gender Differences In Adolescents' Self-concepts 73mentioning
confidence: 99%
“…Although a number of researchers have found that boys perceive themselves as significantly more assertive than girls by early adolescence (Ahlgren & Johnson, 1979;Dusek et al, 1981;Galambos et al, 1990;Leahy & Eiter, 1980;Roberts, Sarigiani, Petersen, & Newman, 1990), others have found no gender differences in adolescent assertiveness, or that adolescent girls report being more assertive or autonomous in their relationships than boys do (Buhrmester et al, 1988;Hibbard, Tao, & White, 1997;Sharabany et al, 1981;Steinberg & Silverberg, 1986). Eccles, Barber, Jozefowicz, Malenchuk, and Vida (1999) found no gender differences in adolescents' self-ratings of leadership or independence while Feldman et al (1981) found that gender differences in assertiveness did not develop until later in life.…”
Section: Gender Differences In Adolescents' Self-concepts 73mentioning
confidence: 99%
“…Overall, boys showed an increase in the link between self-image and achievement from the sixth grade to the eighth grade. Roberts et al (1990) looked at this finding as being consistent with the gender intensification hypothesis which proposed that boys faced greater social pressures for achievement than girls as they moved into adolescence.…”
Section: Stress Management 21mentioning
confidence: 55%
“…Roberts, Sarigiani, Petersen and Newman (1990) studied the relationship between school achievement and self image and found that there were developmental differences for girls and boys during early adolescence. The findings were discussed in terms of gender intensification and social context changes.…”
Section: Stress Management 21mentioning
confidence: 99%
See 2 more Smart Citations